Alpha‐fetoprotein: A biomarker for the recruitment of progenitor cells in the liver in patients with acute liver injury or failure. Issue 10 (19th December 2014) - Kakisaka, Keisuke; Kataoka, Kojiro; Onodera, Mio; Suzuki, Akiko; Endo, Kei; Tatemichi, Yoshinori; Kuroda, Hidekatsu; Ishida, Kazuyuki; Takikawa, Yasuhiro
Abstract : Aim: The optimal conditions for hepatocyte proliferation should be clarified in an attempt to improve the impaired liver regeneration observed in patients with acute liver failure (ALF). In order to evaluate the significance of the serum α‐fetoprotein (AFP). level and prothrombin time international normalized ratio (PT‐INR) as possible biomarkers of the proliferation of liver stem/progenitor cells (LPC) and mature hepatocytes (MH), respectively, we focused on donors of living donor liver transplantation (LDLT) and patients with acute liver injury (ALI), including ALF. Methods: Seventy‐three patients with ALI/ALF and 11 donors for LDLT were evaluated. LPC induction was histologically evaluated using cytokeratin (CK)‐7 staining in 45 ALI/ALF patients. Results: The AFP level was not apparently elevated during the observation period in any of the LDLT donors, whereas the serum AFP levels were substantially increased in the patients with ALI/ALF and significantly correlated with the number of CK‐7 positive LPC in the liver, except for very severe damaged liver. All patients exhibiting an early peak in the AFP level prior to PT‐INR elevation died. Conclusion: The serum AFP level may reflect the induction of LPC in ALI/ALF patients. The substantial and persistent induction of LPC until sufficient regeneration of MH may be needed for a recovery from ALF. We herein demonstrate that the serum AFP level may be a serum marker of LPC in patients with ALI/ALF. A comparison of the serial changes in the AFP levels and PT‐INR in our study patients showed impaired proliferation of LPC and delayed recovery of MH in the patients who died.